2004
DOI: 10.1002/rcm.1590
|View full text |Cite
|
Sign up to set email alerts
|

On‐line laser desorption/ionization mass spectrometry of matrix‐coated aerosols

Abstract: Matrix-assisted laser desorption/ionization (MALDI) was used for the on-line analysis of single particles. An aerosol was generated at atmospheric pressure and particles were introduced into a time-of-flight (TOF) mass spectrometer through a single-stage differentially pumped capillary inlet. Prior to entering the mass spectrometer, a matrix was added to the particles using a heated saturator and condenser. A liquid matrix, 3-nitrobenzyl alcohol (NBA), and a solid matrix, picolinic acid (PA), were used. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…A more powerful approach for on-line bioaerosol analysis is aerosol MALDI mass spectrometr y, as employed by Murray and coworkers. 25,26) Jackson et al 25) reported the on-line MALDI TOF MS analysis of proteinaceous material, whereby the particles were coated in-flight with the matrix nitrobenzyl alcohol.…”
Section: Single Particle Mass Spectrometry Bioaerosol Analysis By Malmentioning
confidence: 99%
“…A more powerful approach for on-line bioaerosol analysis is aerosol MALDI mass spectrometr y, as employed by Murray and coworkers. 25,26) Jackson et al 25) reported the on-line MALDI TOF MS analysis of proteinaceous material, whereby the particles were coated in-flight with the matrix nitrobenzyl alcohol.…”
Section: Single Particle Mass Spectrometry Bioaerosol Analysis By Malmentioning
confidence: 99%
“…33 It is also worth noting that a MALDI study attempting to generate gas-phase complexes of gramicidin S with transition metal cations resulted in protonated ions used as matrix, while metal cation adducts were negligible. 34 In contrast, nontraditional surface matrices such as highly ordered mesoporous WO 3 -TiO 2 showed a clear preference to form [M C K] C adducts.…”
Section: Discussionmentioning
confidence: 99%
“…In aerosol MALDI mass spectrometry, aerosol particles coated with a matrix are either produced from a particle sample suspended in a MALDI matrix solution that is aerosolized or aerosol particles are coated on-the-fly with a vaporized MALDI matrix. Others have explored this approach before obtaining some encouraging results but have also reported challenges in obtaining reproducible mass spectra with aerosol MALDI-MS presumably due to non-uniform matrix coating of aerosol particles (35)(36)(37)(38)(39). Using aerosol MALDI, where peptides were mixed with a MALDI matrix (2,5-Dihydroxybenzoic acid or 2,5 DHB) and aerosolized, we could demonstrate the very high sensitivity of the SPAMS method reaching a 14 zmole detection limit for Gramicidin S, a peptide with molecular mass of 1141 Da (40).…”
Section: Laser Desorption/ionization and Mass Spectrometermentioning
confidence: 98%